Early Warning System For A Strawberry Farm Using Soil Moisture, Temperature, Humidity and Light Intensity Sensors - SAAD, AMNA (Journal of Computing Technologies and Creative Content, 2019)
Early Warning System is a system made with Arduino Uno R3 that is focusing on a strawberry farm to alert the farmers by monitoring the idle soil moisture, temperature, humidity and light intensity of the strawberry plant. The system detects the sensors of the surrounding environment and stores the data collected into Ubidots Cloud. Meanwhile, if the values of soil moisture, temperature, humidity and light intensity of strawberry plant is abnormal, the farmers will take action if the parameters values are not suitable for the plant’s condition. The tests were conducted in three different places, in Level 6 UniKL City Campus, outside housing area and inside housing area. Outside and inside area were conducted in three different times which is on the morning, noon and evening. Ethernet shield is used in this system for sending the sensors values to the cloud. Ubidots cloud showed the data collected and graphs of three sensors used with four variables which are Soil Moisture, Temperature, Humidity and Light Intensity. For this system, the time taken to read every single sensor is 60 seconds and to send the values to the cloud is two seconds. The main reason for the early warning system is to monitor the plant health status to make sure it grows healthy and produce fruits in good condition.